Investigation of the Effects of Polypharmacy on Cognitive Functions: Cohort Study - Bektay, Muhammed Yunus; Gokce, Mustafa; Selvitop, Rabia; Bolat, Erkut; Yildiz, Gulsen Babacan (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Alzheimer’s Disease (AD) is a major concern in growing chronic diseases in the geriatric society and its connection with polypharmacy has not been sufficiently understood. Aim: This Study investigate the association between Alzheimer’s disease and polypharmacy. Methods: A prospective cohort study. Patients with diagnosis of the AD and being older than 55 included in study between March 2017 and September 2017 who applied at the Bezmialem Vakif University Hospital, Istanbul. According to number of used medicine participant divided 3 groups. Age, sex, weight, height were recorded as Socio-demographic variables, a physical and cognitive examination was also performed to determine Mini-Mental State Exam (MMSE) and Katz-Activities of Daily Living (KATZADL) scores. Deterioration of cognitive functions has been associated with alteration of MMSE between 6 months among the groups. Results: We included 79 AD patients and >55 years old into study. Reduction of MMSE scores between six month period were, 1.0 point decrease (p=0.034), 1.29 points decrease (p=0.003) and 2.05 points decrease (p=0.001) respectively. There is statistically significant difference between group I to III, KATZ- ADL (p=0.07). Conclusion: In our study the largest decline in cognitive function seen in group with the highest number of medicine used. Cognitive functions has declined in three groups after 6 months but this cannot be directly linked with polypharmacy. Cognitive and functional status has affected from multiple drug use. There is a need for more detailed and bigger clinical studies about the relationship between polypharmacy and AD.
Keywords: Alzheimer’s disease; Dementia; Polypharmacy; Elderly; KATZ-ADL; MMSE